PEMBERDAYAAN EKONOMI SANTRI MELALUI KOPERASI PESANTREN: ANALISIS HUKUM ISLAM PADA PONDOK PESANTREN AN-NAHDLOH MALAYSIA - Masudi; Mohammad Mahmudi; Masudi; Mohammad Mahmudi (UNIVERSITAS NAHDLATUL ULAMA SUNAN GIRI, 2026)
This study aims to analyze the Islamic law perspective on the development of cooperative entrepreneurship at An-Nahdlah Islamic Boarding School in Selangor, Malaysia. The growth of the sharia economy has encouraged Islamic boarding schools not only to function as religious educational institutions but also as centers for social and economic empowerment through sharia-based cooperatives. This research employs a qualitative method with a normative-empirical approach. The normative approach examines Islamic legal principles related to sharia cooperatives, while the empirical approach is conducted through interviews with school leaders, cooperative managers, and related parties. Secondary data were obtained from books, scientific journals, cooperative documents, and Islamic economic law literature. The findings show that the cooperative operates several business units, including consumer services, student canteens, literacy development, and entrepreneurship education. Its management applies the principles of deliberation, togetherness, and student economic empowerment. From the perspective of Islamic law, the cooperative is in accordance with the principles of syirkah, ta‘āwun, justice, and maqāṣid al-syarī‘ah because it is oriented toward public welfare and community prosperity. The cooperative also seeks to avoid riba, gharar, and maysir through the implementation of sharia contracts. Supporting factors include a religious environment and support from Nahdlatul Ulama organizations, while obstacles include limited capital, weak management professionalism, and regulatory challenges.